Development And Effects Of An Interactive Multimedia Learning Environment (Imle) In Learning Autism Behavioral Symptoms - Dolah, Jasni (2013)
This research was focused to develop and evaluate the effectiveness of a multimedia learning environment with the purpose of increasing learners’ knowledge, awareness as well as perceived motivation towards learning of autism behavioral symptoms. An Interactive Multimedia Learning Environments (IMLE) was developed by integrating relevant learning theories and multimedia principles to provide learners with an interactive content experience. The objective of this research was to study the effects of IMLE as measured by Knowledge Awareness Scale (KAS) in terms of Design Strategies, Gender, Learning Styles and perceived motivation. This research employed a quasiexperimental research with purpose to investigate the effects of two presentation modes: Presentation Mode 1 (Modality Principle) and Presentation Mode 2 (Redundancy Principle). The sample of this study consists of special education pre service teacher who were taking special education courses at local public universities. The total population size of 550 was selected and based on Krejcie and Morgan (1970) table; around 225 samples was selected for the final treatment. The study used several instruments in ensuring the consistency of the outcome during the treatment. The first instrument was the Index of Learning Styles (ILS) developed by Felder and Soloman (1994) with purpose to identify the learning style preferences of the respondents. A second instrument was the Knowledge Awareness Scale (KAS) which requires respondents to self-assess the instrument before and after the presentation modes. The last instrument was the Instructional Material Motivation Scale (IMMS) developed by Keller (2006) which measure the perceived motivation after respondents have completed with KAS 2.